1998
DOI: 10.1038/sj.onc.1202456
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of Ki-ras and elevation of MAP kinase activity during mammary tumor progression in C3(1)/SV40 Tag transgenic mice

Abstract: We have previously documented that transgenic mice expressing SV40 Tag regulated by the rat prostatic steroid-binding protein C3(1) 5'-¯anking region display multistage mammary tumorigenesis. To delineate genetic changes associated with mammary tumor progression, comparative genomic hybridization (CGH) was performed. CGH revealed a consistent gain of the telomeric region of chromosome 6. This region contains the Ki-ras proto-oncogene. Analyses of genomic DNA by Southern blot demonstrated up to 40-fold ampli®ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 17 publications
(33 reference statements)
3
30
0
Order By: Relevance
“…Comparative genomic hybridization has revealed that mammary tumor progression in the C3(1)/Tag transgenic mice is associated with a gain of genomic material from the distal region of mouse chromosome 6 (Liu et al, 1998). We have demonstrated by Southern blot analyses that the ki-ras gene, which is contained within this region of chromosome 6, is ampli®ed up to 30-fold.…”
Section: Genomic Changes During Tumor Progressionmentioning
confidence: 90%
See 1 more Smart Citation
“…Comparative genomic hybridization has revealed that mammary tumor progression in the C3(1)/Tag transgenic mice is associated with a gain of genomic material from the distal region of mouse chromosome 6 (Liu et al, 1998). We have demonstrated by Southern blot analyses that the ki-ras gene, which is contained within this region of chromosome 6, is ampli®ed up to 30-fold.…”
Section: Genomic Changes During Tumor Progressionmentioning
confidence: 90%
“…We have demonstrated by Southern blot analyses that the ki-ras gene, which is contained within this region of chromosome 6, is ampli®ed up to 30-fold. Furthermore, the amplification of ki-ras correlates with increased expression of ki-ras RNA and protein and is associated with increased MAP kinase activity (Liu et al, 1998). In order to determine whether the ampli®cation and overexpression of ki-ras is functionally important for tumor progression in this model, mice carrying the C3(1)/Tag transgene and lacking one allele of ki-ras were generated and studied.…”
Section: Genomic Changes During Tumor Progressionmentioning
confidence: 99%
“…To measure Rapbound GTP, we used the RBD peptide to precipitate Rap´GTP from cell extracts and we measured GTP eluted from Rap using an enzymebased method (Scheele et al, 1995;Pilz et al, 1997;Guha et al, 1996Guha et al, , 1997Prigent et al, 1996;Liu et al, 1998;Egawa et al, 1999;Sharma et al, 1998). To determine the sum of Rap-bound GTP and GDP, we converted Rap´GDP to Rap´GTP by incubating half of the cell extract with 10 mM GTP and then measured Rap´GTP as described above.…”
Section: Measurement Of Rap 1 Activationmentioning
confidence: 99%
“…In experiments where BHK cells were transfected with GST-tagged Rap 1A, the sum of GTP plus GDP bound to Rap 1A was measured by converting GDP to GTP using the enzyme pyruvate kinase (Sharma et al, 1998;Liu et al, 1998;Egawa et al, 1999) and total GTP was then measured.…”
Section: Measurement Of Gtpmentioning
confidence: 99%
“…For instance, the forced expression of c-myc, HER2/neu, and cyclinD1, respectively, under the control of the mammary gland speci®c MMTV-promoter results in mammary gland adenocarcinomas (Muller et al, 1988;Stewart et al, 1984;Wang et al, 1994). Accordingly, the conditional, tissue speci®c depletion of BRCA1 function results in tumor formation (Xu et al, 1999a,b) and the impairment of p53 and RB1 function via expression of SV40 large T antigen under the control of the C3 promoter induces K-ras ampli®cation and tumorigenesis (Liu et al, 1998). As in human cancers, it is likely that tumorigenesis in the mouse is promoted, or at least accompanied by, the acquisition of non-random chromosomal aneuploidies.…”
Section: Introductionmentioning
confidence: 99%